ChemInform Abstract: Pushing the Boundaries of Chemical Protein Synthesis: The Case of Ubiquitin Chains and Polyubiquitinated Peptides and Proteins. Issue 16 (March 2016) - Meledin, Roman; Mali, Sachitanand M.; Brik, Ashraf
Abstract: Review: [57 refs.